2013
DOI: 10.1073/pnas.1312039110
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional coactivator PGC-1α is dispensable for chronic overload-induced skeletal muscle hypertrophy and metabolic remodeling

Abstract: Skeletal muscle mass loss and dysfunction have been linked to many diseases. Conversely, resistance exercise, mainly by activating mammalian target of rapamycin complex 1 (mTORC1), promotes skeletal muscle hypertrophy and exerts several therapeutic effects. Moreover, mTORC1, along with peroxisome proliferatoractivated receptor γ coactivator 1α (PGC-1α), regulates skeletal muscle metabolism. However, it is unclear whether PGC-1α is required for skeletal muscle adaptations after overload. Here we show that altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 43 publications
3
46
1
Order By: Relevance
“…In the same study, we demonstrated that PGC-1α4 is sufficient to induce skeletal muscle hypertrophy. A different group has reported that mice lacking expression of all (known) PGC-1α proteins in skeletal muscle still undergo hypertrophy induced by the synergistic ablation model [63]. We cannot rule out either the existence of additional isoforms that might account for those particular effects or compensatory mechanisms due to the disruption of the Pgc-1α gene since the embryonic state.…”
Section: Challenges and Perspectivesmentioning
confidence: 85%
“…In the same study, we demonstrated that PGC-1α4 is sufficient to induce skeletal muscle hypertrophy. A different group has reported that mice lacking expression of all (known) PGC-1α proteins in skeletal muscle still undergo hypertrophy induced by the synergistic ablation model [63]. We cannot rule out either the existence of additional isoforms that might account for those particular effects or compensatory mechanisms due to the disruption of the Pgc-1α gene since the embryonic state.…”
Section: Challenges and Perspectivesmentioning
confidence: 85%
“…Total protein was recovered from quadriceps muscles as described in Perez‐Schindler, Summermatter, Santos, Zorzato, and Handschin (2013). Equal amounts of protein were migrated on mini‐TGX 4‐20% stain free precast gel (Bio‐Rad, 4568096) and labeled with the in‐gel trihalo compounds under UV for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The binding peak regions were aligned with orthologous regions from 6 other mammalian species-human (hg18), rhesus macaque (rheMac2), dog (canFam2), horse (equCab1), cow (bosTau3), and opossum (monDom4)-using TCoffee (18). A collection of 190 mammalian regulatory motifs (position weight matrices [WMs]) representing the binding specificities of approximate 350 mouse TFs (in many cases, sequence specificities of multiple closely related TFs were represented with the same WM) were downloaded from the SwissRegulon website (19). TFBSs for all known motifs were predicted using the MotEvo algorithm (20) on the alignments of all 7,512 peak sequences.…”
mentioning
confidence: 99%
“…Subsequently, probes were classified as expressed or nonexpressed by using the "Mclust" R package (22), and after removal of nonexpressed probes, the intensity values were quantile normalized across all samples. Using mapping of the probes to the UCSC collection of mouse mRNAs, probes were then associated with a comprehensive collection of mouse promoters available from the SwissRegulon database (19). The log 2 expression level of a given promoter was calculated as the weighted average of the expression levels of all probes associated with it.…”
mentioning
confidence: 99%